THE USE OF ANGULAR VELOCITY VECTOR IN SHELL STRUCTURES - CHEBILI, R.; MEZGHICHE, B.; MELLAS, M; IZEMOUREN, O. (Courrier du Savoir; Vol. 6 (2005): Courrier du Savoir, 2014)
In the following work, the principle of deformation is investigated using a new parameter called the angular velocity. The deformed element of surface is fully defined by this new parameter that is whenever the element of the reference surface undergoes a motion the three components of angular velocity define completely this motion.